2015
DOI: 10.1002/cphc.201500498
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Molecular Orbital–Climbing Image–Nudged Elastic Band Method to Analyze Chemical Reactions Including Nuclear Quantum Effect

Abstract: To analyze the H/D isotope effects on hydrogen transfer reactions in XHCHCHCHY↔XCHCHCHYH (X, Y=O, NH, or CH2 ) including the nuclear quantum effect of proton and deuteron, we propose a multicomponent molecular orbital-climbing image-nudged elastic band (MC_MO-CI-NEB) method. We obtain not only transition state structures but also minimum-energy paths (MEPs) on the MC_MO effective potential energy surface by using MC_MO-CI-NEB method. We find that nuclear quantum effect affects not only stationary-point geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 14 publications
2
36
0
Order By: Relevance
“…Several groups also have developed their own multicomponent methods and successfully analyzed interesting chemical and physical phenomena . Quite recently, we analyzed the nuclear quantum effect on chemical reactions, that is, H/D kinetic isotope effect (KIE) on the rate constants and minimum energy path on the MCMO effective potential energy surface of the several intramolecular hydrogen transfer reactions with the aid of MCMO‐climbing image‐nudged elastic band (CI‐NEB) method …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups also have developed their own multicomponent methods and successfully analyzed interesting chemical and physical phenomena . Quite recently, we analyzed the nuclear quantum effect on chemical reactions, that is, H/D kinetic isotope effect (KIE) on the rate constants and minimum energy path on the MCMO effective potential energy surface of the several intramolecular hydrogen transfer reactions with the aid of MCMO‐climbing image‐nudged elastic band (CI‐NEB) method …”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29][30][31][32][33] Quite recently, we analyzed the nuclear quantum effect on chemical reactions, that is, H/D kinetic isotope effect (KIE) on the rate constants and minimum energy path on the MCMO effective potential energy surface of the several intramolecular hydrogen transfer reactions with the aid of MCMO-climbing image-nudged elastic band (CI-NEB) method. [34] In the actual MCMO calculations, we adopt the basis set expansion to nuclear orbitals, as well as the electronic ones. Gaussian-type functions (GTFs) are widely used as the electronic and nuclear basis function due to the ease of integral calculations.…”
Section: Introductionmentioning
confidence: 99%
“…The TS structures are also relaxed by including NQE of proton and deuteron. We have already reported that the geometrical relaxation of stationary point structures is important factor for the adequate discussion of the H/D isotope effect on potential energy profiles . Although the difference between zero‐point vibrational energies of proton and deuteron can be taken into account with the aid of the conventional QM methods, geometrical changes because of deuterium substitution is basically not considered in conventional QM calculations.…”
Section: Resultsmentioning
confidence: 99%
“…We have already reported that the geometrical relaxation of stationary point structures is important factor for the adequate discussion of the H/D isotope effect on potential energy profiles. [20] Although the difference between zeropoint vibrational energies of proton and deuteron can be taken into account with the aid of the conventional QM methods, geometrical changes because of deuterium substitution is basically not considered in conventional QM calculations. By representing these H/D isotope effect on geometrical parameters (geometrical H/D isotope effect) using MC_QM method, we can apply the ASM [32] to analyze H/D isotope effect on the calculated activation barriers in detail.…”
Section: Multicomponent Quantum Mechanics (Mc_qm) Methodsmentioning
confidence: 99%
See 1 more Smart Citation